2020
DOI: 10.1038/s41593-020-0652-4
|View full text |Cite
|
Sign up to set email alerts
|

Memory trace interference impairs recall in a mouse model of Alzheimer’s disease

Abstract: In Alzheimer's disease (AD), hippocampus-dependent memories underlie an extensive decline. The neuronal ensemble encoding a memory, termed engram, is partly recapitulated during memory recall. Artificial activation of an engram can restore memory in a mouse model of early AD, but its fate and the factors that render the engram nonfunctional are yet to be revealed. Here we used repeated two-photon in vivo imaging in fosGFP transgenic mice that performed a hippocampus-dependent memory task. We found that the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 55 publications
6
47
0
Order By: Relevance
“…In slices from 5xFAD/1;Thy1-GCaMP6f/1 mice, ensembles were larger and less similar compared with control Thy1-GCaMP6f/1 littermates, suggesting that aberrant cell participation may disrupt the neuronal orchestra in AD mice. This is consistent with a recent report by Poll et al (2020), which showed that activation of additional ensembles interfered with memory recall in another model of AD. Interestingly, Caccavano et al (2020) observed different alteration of firing dynamics of deep and superficial CA1 pyramidal cells.…”
Section: Introductionsupporting
confidence: 94%
“…In slices from 5xFAD/1;Thy1-GCaMP6f/1 mice, ensembles were larger and less similar compared with control Thy1-GCaMP6f/1 littermates, suggesting that aberrant cell participation may disrupt the neuronal orchestra in AD mice. This is consistent with a recent report by Poll et al (2020), which showed that activation of additional ensembles interfered with memory recall in another model of AD. Interestingly, Caccavano et al (2020) observed different alteration of firing dynamics of deep and superficial CA1 pyramidal cells.…”
Section: Introductionsupporting
confidence: 94%
“…Our results support the concept that cFos+ neurons in DG encode an episode, but not a spatial position (Hainmueller & Bartos, 2020). The disconnect between cFos expression and place cell activity has also been reported in a recent study of CA1 pyramidal cells (Poll et al, 2020;Tanaka et al, 2018) and is therefore not a specific property of DG granule cells.…”
Section: Which Factors Control Cfos+ Ensemble Reactivation In Dg?supporting
confidence: 91%
“…This is even more remarkable when considering that reversal did not decreased the overall activity of the CA3ab in 4D animals, but still this area showed levels of reactivation lower than what expected by chance. These improvements may be highly relevant in the context of neurodegenerative disorders causing memory interference, as recently demonstrated in models of Alzheimer disease (Poll et al, 2020).…”
Section: Discussionmentioning
confidence: 94%